REGELUNG VON GEBÄUDEHEIZSYSTEMEN MIT FREI PROGRAMM:IERBAREN STROMKREISEN - Kancsár, János (Periodica Polytechnica Mechanical Engineering, 1986)
The study intends to bring up to date analogous heating control systems. On the basis on the literature the first chapter deals with the changes in building structure. The second one deals with analogous heating control systems used in wide-rage. The following part describes a new heating control system based on digital computer regulation. In conclusion the paper indicates some further development possibilities.